Exploring the therapeutic potential of Nelumbo nucifera leaf extract against amyloid-beta-induced toxicity in the Caenorhabditis elegans model of Alzheimer’s disease - Wen, Yong-Ping; Fu, Hai-Jun; Chen, Qin; Lan, Cai; Qin, Da-Lian; Wu, Jian-Ming; Wu, An-Guo; Zhou, Xiao-Gang (Frontiers in Pharmacology, 2024)
Alzheimer's disease (AD) presents a global health crisis with limited therapeutic options, urging the exploration of alternative strategies. A pivotal pathology in AD involves amyloid beta (Aβ) aggregation, and addressing Aβ aggregation alongside oxidative stress is vital for effective intervention. Natural compounds from medicinal and food sources have emerged as potential preventive and therapeutic agents, among which Nelumbo nucifera leaf extract (NLE) shows promising properties. In this study, we investigated NLE's potential in countering AD and elucidated the underlying mechanisms using transgenic Caenorhabditis elegans (C. elegans) models. The results revealed that NLE significantly reduced paralysis rates in CL4176 and CL2006 worms while enhancing food-searching capabilities in CL2355 worms. Furthermore, NLE attenuated Aβ aggregate accumulation and mitigated Aβ-induced oxidative stress in C.elegans. Moreover, NLE extended lifespan of worms under oxidative and thermal stress conditions, concurrently elevating the expression of stress-resistance-related proteins (SOD-3, GST-4, HSP-4, and HSP-6). Additionally, NLE induced autophagy in C. elegans, as evidenced by reduced p62 levels in BC12921 worms and the formation ofLGG-1 + structures in DA2123 worms. However, RNAi-mediated inhibition of autophagy-related genes, including bec-1 and vps-34, negated the protective effects of NLE against Aβ-induced paralysis and aggregate accumulation, suggesting that NLE ameliorates Aβ-induced toxicity by activating autophagy in C. elegans. Together, these findings underscore NLE as a promising candidate for further investigation in AD management, offering multifaceted approaches to mitigate AD-related pathology and stress-related challenges.